2004
DOI: 10.4049/jimmunol.173.10.5963
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Adhesion to Cholinergic IMR-32 Cells Protects against Induced Neuronal Apoptosis

Abstract: Eosinophils release a number of mediators that are potentially toxic to nerve cells. However, in a number of inflammatory conditions, such as asthma and inflammatory bowel disease, it has been shown that eosinophils localize to nerves, and this is associated with enhanced nerve activity. In in vitro studies, we have shown that eosinophil adhesion via neuronal ICAM-1 leads to activation of neuronal NF-κB via an ERK1/2-dependent pathway. In this study, we tested the hypothesis that eosinophil adhesion to nerves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…Thus it is suggested that immune cell-derived mediators cause depolarization of neurons and decrease their membrane resistance, 29 potentiate transmitter release, 30 and promote survival. 31 Conversely, activated afferent nerve fibers amplify airway inflammation by means of local release of neuropeptides, which then is also termed neurogenic inflammation. 7 Neuropeptides promote the chemotaxis, activation, and degranulation of eosinophils; increase lymphocyte proliferation and adhesion; and cause an imbalance in T H 1/T H 2-derived cytokines in favor of a T H 2 profile.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is suggested that immune cell-derived mediators cause depolarization of neurons and decrease their membrane resistance, 29 potentiate transmitter release, 30 and promote survival. 31 Conversely, activated afferent nerve fibers amplify airway inflammation by means of local release of neuropeptides, which then is also termed neurogenic inflammation. 7 Neuropeptides promote the chemotaxis, activation, and degranulation of eosinophils; increase lymphocyte proliferation and adhesion; and cause an imbalance in T H 1/T H 2-derived cytokines in favor of a T H 2 profile.…”
Section: Discussionmentioning
confidence: 99%
“…The multidomain proapoptotic proteins BAX and BAK together constitute a requisite gateway to apoptotic cell death, because cells doubly deficient for these proteins are resistant to several different intrinsic death stimuli [15]. Therefore, BAX, BCL2, and cleaved CASP3 are widely used to assess apoptosis [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that eosinophil adhesion to IMR-32 cells confers protection on nerve cells from apoptosis induced either by proinflammatory cytokines (tumor necrosis factor, IL-1␤, and interferon-␥) or by serum deprivation (17). This is consequent to eosinophil adhesion to IMR-32 cells because eosinophil membrane preparations, which lacked eosinophil granule products, conferred similar protection to that provided by whole eosinophils.…”
mentioning
confidence: 99%
“…This is consequent to eosinophil adhesion to IMR-32 cells because eosinophil membrane preparations, which lacked eosinophil granule products, conferred similar protection to that provided by whole eosinophils. Protection was dependent on adhesion via both ICAM-1 and VCAM-1 and on ERK 1/2 but not p38 activation (17). Having identified the role of surface adhesion per se, we have now attempted to identify the actions of the products released from the eosinophils.…”
mentioning
confidence: 99%